QR Code-Based Smart Document Implementation Using Distributed Database And Digital Signature - Ayub, Waqas; Winarno, Idris; Sudarsono , Amang (The Indonesian Journal of Computer Science, 2024)
In digitized world, digital documents are essential for information sharing. However, some organizations continue to place their reliance in traditional hard-copy formats concerning about the legitimacy of documents. This study presents an innovative approach to document verification with digital signatures, distributed databases, and QR codes. Using a two-step process for data integrity and document authentication, the study approach entails developing a Smart Document with a QR code and digital signature. For increased security and scalability, the system design distributes hash fragments among several databases using the hash split approach. The system's excellent performance, resistance to sluggish HTTP-based attacks, and effectiveness in document verification are highlighted by the results and debates. The report ends with recommendations for future improvements to strengthen the system's resilience, like implementing more secure database engines and enhancing fault tolerance. In conclusion, this method offers a viable way to verify documents in hardcopy and electronic formats in a secure and scalable manner.